The Influence of Entrepreneurship on Economic Independence of Students with Internal Locus of Control as a Moderation Variable in an Islamic Business Perspective - Latifah, Latifah; Ridwansyah, Ridwansyah; Selvina, Mia (Indonesian Interdisciplinary Journal of Sharia Economics (IIJSE), 2026)
This study aims to analyze the effect of entrepreneurship on the economic independence of students at the Raden Intan State Islamic University of Lampung, with Internal Locus of Control as a moderating variable. A quantitative approach was used, employing Partial Least Squares Structural Equation Modeling (PLS-SEM). Data were collected through an online questionnaire completed by 96 respondents who were entrepreneurs at the State Islamic University Raden Intan Lampung. Based on the background of this article, the method used in this study was a descriptive method with a quantitative approach. The results showed that entrepreneurship had a positive and significant effect on economic independence. Meanwhile, internal locus of control was not able to moderate the relationship between entrepreneurship and economic independence. These findings indicate that the higher the level of student involvement in entrepreneurial activities, the greater their financial independence. From an Islamic business perspective, entrepreneurship and internal locus of control are noble efforts to achieve economic independence. However, they must be complemented by Tawakkal (trust in God) to ensure sustainability, avoid arrogance, and reject resignation. This study recommends expanding the research object so that it is not limited to certain students, allowing the generalization of results to be tested in a wider area.